PENGARUH PENERAPAN SISTEM E-FILING, E-BILLING DAN PEMAHAMAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA SURABAYA TEGALSARI - Nurchamid, Muhammad; Sutjahyani, Dewi (JEA17: Jurnal Ekonomi Akuntansi, 2018)
AbstractThis study aims to determine: (1) the influence of the application of e-filing system at the Pratama Surabaya Tegalsari tax service office (2) the effect of implementing e-billing system on Pratama Surabaya Tegalsari tax service office (3) the influence of understanding taxation on taxpayer compliance at the office Pratama tax service in Surabaya Tegalsari (4) the influence of the application of e- filing, e-billing and taxation understanding of taxpayer compliance at the Pratama Surabaya Tegalsari tax service office. This study uses primary data by distributing online questionnaires aimed at taxpayers who meet the criteria determined by the researcher. The population in this study are taxpayers who are registered as e-filing and e-billing taxpayers at the Pratama tax service office in Surabaya Tegalsari. In this study using a sample of 100 respondents, the sampling method uses self- selected respondents, ie someone who chooses himself to participate becomes a respondent voluntarily of his own volition because of interest in the research being conducted. The results of this study indicate that (1) the application of e-filing system does not affect taxpayer compliance (2) the application of e-billing system does not affect taxpayer compliance (3) understanding of taxation does not affect taxpayer compliance (4) implementation of e-system -filing, e-billing and understanding of taxation have a simultaneous effect on tax compliance at the Pratama Tax Office Surabaya Tegalsari. Keywords: e-filing, e-billing, understanding of taxation, compliance of taxpayers.